Socialization of the Benefits and Tips For Facing TOEFL Listening for Tamsis Senior High School Students - Damanik, Jenny Nur Idill Rohan; Tifani, Juliana; Inda, Tri; Marpaung, Titin; Herman, Herman (Universitas Ibn Khaldun, 2025)
This outreach program was designed to enhance the awareness, understanding, and motivation of Grade XI students at Tamsis Senior High School in facing the TOEFL Listening section. As English becomes increasingly vital in global academic and professional environments, improving students’ listening proficiency is a critical step toward success. The program introduced the concept of the TOEFL, its purposes, benefits, and different types (iBT, ITP, Prediction). It also focused on common listening challenges and specific strategies to address them. These included concentrating on the second speaker’s response, recognizing paraphrased or synonymous vocabulary, and avoiding answer choices based on similar-sounding words. The implementation phase featured interactive presentations, audio-based simulations, and group discussions. Students practiced answering real TOEFL-style questions and received immediate feedback. The use of PowerPoint, Google Forms, and authentic audio materials fostered engagement and improved comprehension. During the evaluation phase, students reported increased confidence and a stronger motivation to continue practicing. They also demonstrated a clearer understanding of TOEFL Listening expectations and test structure. The interactive format allowed for active participation, peer learning, and personalized strategy application. As a result, the outreach program proved effective in equipping students with the necessary tools to approach TOEFL Listening tasks with greater competence and self-assurance. It is recommended that similar initiatives be replicated in other schools to help students prepare early for English proficiency tests. By combining strategic instruction, real-world materials, and motivational support, this program offers a practical model for developing listening skills that are essential for academic and professional advancement.